Frequency responses of transformer winding deformations based on finite element modeling under transient overvoltage impulses - Murthy, Avinash Srikanta (2020)
Frequency Response Analysis (FRA) is one of the best approaches to detect the mechanical integrity of transformer windings. FRA can be measured on-site or simulated based on the transformer’s design information. The calculations of Resistance (R), Inductance (L), Capacitance (C) and Conductance (G) parameters are essential to simulate the frequency responses based on transfer function and Multi-conductor Transmission Line (MTL) methods. These methods however could not provide detail conditions of the individual windings as well as the cause and effect of mechanical movements. The known causes such as the lightning strikes or switching events could lead to the amplification/attenuation of the overvoltages along the windings and subsequently result in abnormal voltage stresses. The electromagnetic fields could be generated and result in electromechanical effects which need to be classified. Hence, this project is carried out to address the stated issues. First, an alternative approach to extract transformer’s winding RLCG parameters based on Finite Element Method (FEM) was proposed. The C and G were computed based on Fast Multipole Method (FMM) and Method of Moment (MoM) through quasi-electrostatics approach. The AC resistances and inductances were computed based on MoM through quasi-magnetostatics approach. Maxwell's equations were used to compute the DC resistances and inductances. Based on the FEM computed parameters, the frequency response of the winding was simulated through the Bode plot function. The simulated frequency response by FEM model was compared with the simulated frequency response based on the MTL model and the measured frequency response of HV winding for 33/11 kV transformer. Next, the resonant oscillations of HV layer and disc types windings for 11/0.415 kV and 33/11 kV transformers under different cases of lightning and switching impulses were analyzed. The impulse overvoltage were applied to the HV winding and the resonant oscillations were simulated for each of the layers and discs with consideration on different placement configurations of an electrostatic shield. The effects of different magnitudes of standard lightning impulse on the mechanical displacements and deformations of HV windings of an 11/0.415 kV transformer were also examined based on FEM. The resultant electromagnetic forces acting in axial and radial directions were computed and induced to the winding structure. It is found that the simulated frequency response by FEM model is quite close to measured frequency response at low and mid frequency regions based on Root Mean Square Error (RMSE) and Absolute Sum of Logarithmic Error (ASLE). The voltage stresses along the windings are more linear and the resonant oscillations are the lowest once a floating shield is placed between the HV and LV windings of the 11/0.415 kV and 33/11 kV transformers under different cases of lightning and switching impulses based on error of the slope (SEb). It is observed that the outer column supports of the winding structure for 11/0.415 kV transformer experiences apparent electromechanical stresses and radial buckling deformations are observed. The life and lightning overvoltage impulse withstand capability of the winding is estimated to be 1 × 106 impulse cycles which is lower than the design life of 1 × 109 for the copper conductors based on fatigue life and Von-Mises criterion.